- #1

Aaron8153

## Main Question or Discussion Point

I know that:

yI(x,t) = AI sin [k1( x - v1t )]

yR(x,t) = AR sin [k1( x - v1t )]

yT(x,t) = AT sin [k1( x - v2t )]

W1 = W2

k1v1 = k2v2

I am unsure about how to prove that AI = AT + AR

Where AI, AT, and AR are the different amplitudes of the incident, transmitted, and reflected waves.

yI(x,t) = AI sin [k1( x - v1t )]

yR(x,t) = AR sin [k1( x - v1t )]

yT(x,t) = AT sin [k1( x - v2t )]

W1 = W2

k1v1 = k2v2

I am unsure about how to prove that AI = AT + AR

Where AI, AT, and AR are the different amplitudes of the incident, transmitted, and reflected waves.